To make the two expressions equivalent, we need to find the value of y that will make the left side equal to the right side.
First, we need to simplify the left side of the equation:
yb – 6 + 7 + 2b – 3b + 1 = 5b + 2
Combine like terms:
yb + 2b – 3b – 6 + 7 + 1 = 5b + 2
yb – 1 = 5b + 2
Next, let's isolate the variable y by moving all terms involving y to one side of the equation:
yb – 1 = 5b + 2
Subtract 5b from both sides:
yb - 5b - 1 = 2
Now we have:
-4b = 3
Divide both sides by -4 to solve for b:
b = -3/4
Therefore, the value of y that would make the expression yb−6+7+2b−3b+1 equivalent to 5b+2 is -3/4.
What value of y would make the expression yb−6+7+2b−3b+1 equivalent to 5b+2?(1 point
1 answer